2000
DOI: 10.1093/embo-reports/kvd092
|View full text |Cite
|
Sign up to set email alerts
|

Finding nuclear localization signals

Abstract: A variety of nuclear localization signals (NLSs) are experimentally known although only one motif was available for database searches through PROSITE. We initially collected a set of 91 experimentally verified NLSs from the literature. Through iterated 'in silico mutagenesis' we then extended the set to 214 potential NLSs. This final set matched in 43% of all known nuclear proteins and in no known non-nuclear protein. We estimated that >17% of all eukaryotic proteins may be imported into the nucleus. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
532
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(556 citation statements)
references
References 24 publications
(38 reference statements)
19
532
2
3
Order By: Relevance
“…In short, amino acid sequences for those proteins identified by MS were extracted from the SOL genomics protein database v. ITAG2.4 (Tomato Genome, 2012). This data set was subjected to predictnls (default settings) (Cokol et al ., 2000) and nlstradamus (two‐state model; posterior threshold 0.6) (Nguyen Ba et al ., 2009) to identify proteins with nuclear localization signals, and the Nucleolar Localization Sequence Detector ( nod ) (default settings) (Scott et al ., 2010, 2011) to identify proteins with nucleolar localization signals. Additionally, we used wolf psort (plant) (Horton et al ., 2007) and filtered all proteins marked as nuclear.…”
Section: Methodsmentioning
confidence: 99%
“…In short, amino acid sequences for those proteins identified by MS were extracted from the SOL genomics protein database v. ITAG2.4 (Tomato Genome, 2012). This data set was subjected to predictnls (default settings) (Cokol et al ., 2000) and nlstradamus (two‐state model; posterior threshold 0.6) (Nguyen Ba et al ., 2009) to identify proteins with nuclear localization signals, and the Nucleolar Localization Sequence Detector ( nod ) (default settings) (Scott et al ., 2010, 2011) to identify proteins with nucleolar localization signals. Additionally, we used wolf psort (plant) (Horton et al ., 2007) and filtered all proteins marked as nuclear.…”
Section: Methodsmentioning
confidence: 99%
“…genome.jp/). Nuclear localization signals were predicted using the algorithm of Cokol et al (2000) at (http://cubic.bioc.columbia. edu/services/predictNLS/) and signal peptides were identified with (http://www.cbs.dtu.dk/services/).…”
Section: Methodsmentioning
confidence: 99%
“…Since the PLP/DM20 C-terminus portion is out of frame in the mutant, it is possible that a nuclear localization signal (NLS) might have inadvertently been created. However, neither Plp jp PLP nor wild-type PLP contains an NLS when analyzed with a program that searches for NLS (http://cubic.bioc.columbia.edu/predictNLS) [41,42]. Furthermore Anderson et al [40] demonstrated that expression of the Plp jp PLP protein in Schwann cells did not prevent expression of wild type PLP protein.…”
Section: Downregulation Of the Plp Gene And The Plp(+)z Transgene Inmentioning
confidence: 99%